Caracterização de parâmetros reprodutivos em um modelo murino de mucopolissacaridose tipo I - Mendes, Ana Beatriz Barbosa [UNIFESP] (2018)
Mucopolysaccharidosis type I (MPS I) is a lysosomal storage disorder characterised by α-L-iduronidase (IDUA) deficiency. IDUA is responsible for the breakdown of glycosaminoglycans (GAGs), specifically dermatan sulphate and heparan sulphate and, when absent, causes the storage of these GAGs in both intracellular and extracellular compartments of several tissues. Patients with MPS I tend to have a short life expectancy when untreated. However, due to recent therapeutic advancements, many are reaching adult life and may chose to bear children. Therefore, it is relevant that the effects of MPS I on the female reproductive system and function be investigated. Aims: To characterise the female reproductive system and function in a murine model of MPS I. Methods: 3-month-old knockout and wild-type female mice underwent sexual behaviour and open field assays and were later euthanised. 6-month-old mice were also euthanised, but not tested behaviourally. Their reproductive organs and blood were collected. The uteri and ovaries were stained with haematoxylin and eosin and colloidal iron. The sulphated GAGs present in both organs were quantified through a colorimetric assay. Plasmatic steroidal hormones concentrations were determined through ELISA. Results: The knockout females had an equivalent performance to the control females in the sexual behaviour assay. They also presented lower mobility in the open field test when compared to controls. Fibrosis and GAG storage were seen in uterine and ovarian tissue of older knockout mice but were absent in their younger or control counterparts. GAG levels were higher only in the ovary of 3-month-old knockouts. Conclusion: Despite their decreased mobility, MPS I female mice express normal sexual behaviour. While their reproductive organs show severe morphological compromise, especially in older individuals, their sexual hormone production does not seem to be affected.